Persepsi Guru dalam Kaitannya dengan Implementasi Pendidikan Lingkungan di Sekolah Dasar di Sekitar Hutan Gunung Salak Endah - Resti Meilani; E.K.S Harini Muntasib; Soeryo Adiwibowo (Media Konservasi, 2012)
Research and information on teachers’ perception of environment and environmental education (EE) in Indonesian context were insufficient.  Therefore, this research aimed at identifying teachers’ perception of environment and EE, as well as the influencing factors.  Results showed that: (1) Teachers from forest margin areas had limited environmental perception; (2) Most of them had positive perception on EE implementation; however they viewed their competence and self-efficacy as being low.  (3) Differences in EE perception among teachers were influenced by their educational background, non formal education, level of teaching difficulties from the grade they taught, and organizational experiences. Keywords: teacher, perception, environmental education, elementary school, forest margin area, Gunung Salak Endah